Students’ Self-Perceived Multiple Intelligences and their Parents’ Education - Shahzada, Gulap; Ghazi, Safdar Rehman; Khan, Habib Nawaz; Zaman, Safeer; Shah, Tahir (Mediterranean Journal of Social Sciences, 2011)
This study aimed at to investigate the relationship between parent’s education and students’ self perceived multiple intelligences.All Students of 1st years in district Bannu constituted population of the study. Using multistage random sampling 379 male and 335female all together 714 students were selected as a sample of the study. A significant correlation was found between Students’ self-perceivedverbal/linguistic, logical/mathematical, musical intelligence and their parents’ education, and nonsignificant correlation was found betweenstudents’ self-perceived bodily/kinesthetic, interpersonal, intrapersonal, naturalistic intelligence and their parents’ education. There was anegative correlation between students’ self-perceived bodily/kinesthetic intelligence and their parents’ education. On the basis of the findingsit was recommended that children may be provided various opportunities so they may develop properly their multiple intelligences.Government may make such policies regarding education where education of every citizen is guaranteed.